Photoredox Organic Synthesis Employing Heterogeneous Photocatalysts with Emphasis on Halide Perovskite. Issue 58 (17th September 2020) - Lin, Yixiong; Guo, Jun; San Martin, Jovan; Han, Chuang; Martinez, Ramon; Yan, Yong
Abstract: Lately, heterogeneous semiconductor materials have been explored as an emerging type of efficient photocatalyst for photoredox organic synthesis. Among these semiconductors, lead halide perovskite materials demonstrate unique properties towards excellent charge separation and charge transfer, extremely long charge carrier migration, high efficiency in visible light absorption, and long excited states lifetimes, etc., as proved in ground‐breaking solar cell applications, garnering necessary merits for an efficient catalytic system for photoredox organic reactions. Here, the latest progress in heterogeneous semiconductor materials towards this endeavor is examined, with particular emphasis on lead halide perovskite nanocrystals (NCs) in photocatalytic organic synthesis. Abstract : Leading light : Heterogeneous semiconductor materials have been explored as an emerging type of efficient photocatalyst for photoredox organic synthesis, and hybrid halide perovskite materials are among a unique type that demonstrates exceptional photophysical properties. Here, the latest progress in heterogeneous semiconductor materials towards this endeavor is examined, with particular emphasis on the lead halide perovskite nanocrystals for photocatalytic organic synthesis.